Modern Approaches to Analysis of Technical and Tactical Actions of Skilled Volleyball Players - Iryna Oliinyk (OVS LLC, 2021)
Purpose. To develop an algorithm of special analysis for improving the training process, based on the identification of indicators of technical and tactical actions in the competitive activity of skilled volleyball players.